Bone marrow mesenchymal stem cell-derived exosomes alleviate DSS-induced inflammatory bowel disease in mice through inhibiting intestinal epithelial cell pyroptosis via delivery of TSG-6 - Wu, Bihua; Su, Shuangyan; Wang, Xianyu; Li, Yuwei; Mei, Zhenghao; Lou, Fenglin; Guo, Le (Frontiers in Immunology, 2025)
BackgroundInflammatory bowel disease (IBD), characterized by chronic intestinal inflammation and epithelial barrier dysfunction, remains a therapeutic challenge due to the limitations of current treatments, including drug resistance and invasive surgical risks. Emerging evidence implicates intestinal epithelial cells (IECs) pyroptosis as a key contributor to IBD progression. Bone marrow mesenchymal stem cell exosomes (BMSCs-Exo) exhibit anti-inflammatory and tissue-reparative potential, yet the role of tumor necrosis factor-stimulated gene 6 (TSG-6), a critical anti-inflammatory mediator in BMSCs-Exo, in modulating pyroptosis and intestinal barrier integrity remains unexplored. This study investigates the role of TSG-6 contained in mesenchymal stem cell-derived exosomes (MSCs-Exo) in alleviating IBD by modulating the pyroptosis signaling pathway in IECs.ResultsIn this study, TSG-6-enriched BMSCs-Exo significantly alleviated intestinal inflammation and pyroptosis in murine IBD models. BMSCs-Exo administration reduced NLRP3 inflammasome activation, suppressed Caspase-1-mediated Gasdermin D (GSDMD) cleavage, and decreased pro-inflammatory cytokine release (IL-1β, IL-18). Notably, TSG-6 knockdown in BMSCs-Exo abolished these protective effects, confirming its essential role in blocking the NLRP3/Caspase-1/GSDMD axis. Furthermore, BMSCs-Exo restored intestinal barrier integrity by upregulating tight junction proteins (e.g., ZO-1, occludin) and reducing epithelial permeability. In vitro experiments revealed that BMSCs-Exo directly inhibited pyroptosis in IECs, attenuating cell membrane rupture and inflammatory cascade amplification.ConclusionThis study identifies TSG-6 as a pivotal mediator in BMSCs-Exo that disrupts pyroptosis-driven IBD pathogenesis by targeting NLRP3 inflammasome activation. The findings highlight BMSCs-Exo as a cell-free therapeutic strategy to mitigate intestinal inflammation and barrier damage, offering advantages over traditional MSCs-based therapies in safety and specificity. By elucidating the TSG-6/NLRP3 regulatory axis, this work provides a novel framework for developing exosome-engineered treatments for IBD and other pyroptosis-related inflammatory disorders.